أثر تطويش القمة النامية و الرش الورقي ببعض المخصبات العضوية في نمو وإنتاج نبات البامياء (Abelmoschus esculentus Ls.) - سليمان نصر; الحاجي علا (Latakia University Journal -Biological Sciences Series, 2016)
نفذ البحث في مشتل كلية الزراعة جامعة تشرين, خلال الموسم الزراعي 2013-2014 ,على صنف البامياء المحلي, لدراسة أثر تطويش القمة النامية و الرش الورقي ببعض المركبات الدبالية والأحماض الامينية في نمو و إنتاج نبات البامياء , تضمنت التجربة 8 معاملات في أربع مكررات لكل معاملة وبمعدل 14 نبات في المكرر الواحد وفق تصميم القطاعات العشوائية الكاملة,واستخدم نوعين من المخصبات العضوية ألترا هيومك أسيد , Altra humic acide(مركب دبالي) وأمينو فيغا 25 Amino vega (أحماض أمينية). أظهرت النتائج أن رش النباتات بالمركبات العضوية الدبالية والاحماض الامينية مع تطويش القمة النامية قد حققت اعلى القيم في بعض الصفات الثمرية المدروسة لاسيما في عدد الثمار على النبات وانتاج النبات . كما أوضحت النتائج أن لتطويش القمة النامية مع الرش بالمخصبات العضوية أثرا ايجابيا في بعض صفات النمو الخضري كطول الساق , وعدد الفروع , وعدد الاوراق مع عدم وجود فروق بين المعاملات المتفوقة . An experiment was conducted in agricultural college arboretum that belong to tishreen university on okra during the growing season of 2013-2014 to investigate the effect of spraying by organic fertilizers and growing point pinching on the growth and yield. The experiment include 8 treatments as control (without spraying by organic fertilizers or growing point pinching), two kinds of organic fertilizers (ultra humic acid and amino vega) with or without growing point pinching. Plots were completely randomized over the experimental area having four replicates for each treatment. Each replicate contained 14 plants. Results showed that the highest values of vegetative growth parameters are stem length branch number ,leave number per plant due to the interaction between pinching of growing point and spraying by ultra humic acid and amino vega . The experiment results revealed also ,that the highest yield and The largest number and weight of fruits was produced from growing point pinching and spraying by ultra humic acid and amino vega, compared to all other treatments.